Between democracy and barbarism, Colombia, two centuries in search of governability (2011)
Nestor Hernando Parra shared with me in Valencia his book "Between democracy and barbarism. Colombia two centuries in search of governability". Dr. Parra's rigorous research scientifically addresses numerous issues in Colombian history. Anyone who wants to know in depth the past and present of the Republic should read it. In this article different topics are highlighted, such as: Iniquity talks about Santanderism that sharpened in Colombia has led us to the fact that human rights, although they were adopted in legal texts, were not applied. " Social Darwinism, I agree that education is the trump card to build social equity. Corporatism, Parra maintains that in Colombia there has been a kind of corporate corporatism in which organized economic groups practically exercise a co-government. The exclusive cleracalismo, Narrates the violence between conservatives and liberals. Similarly, issues such as corruption, predatory neoliberalism, armed conflict, empire, lacerating poverty, utopian social democracy, drug trafficking, foreign debt, etc.